Dampak Kompetensi dan Komunikasi Interpersonal Terhadap Kualitas Layanan Literasi Informasi: Peran Mediasi Pengalaman Mahasiswa Tugas Akhir - Raden Panji Yohanes Udik Esbiantoro; Liosten Rianna Roosida Ully Tampubolon (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2026)
The purpose of this study is to examine the influence of librarians’ competence and interpersonal communication on the quality of information literacy services, with the experience of final-year students as a mediating variable. Using a quantitative approach, the study employed Partial Least Square-Structural Equation Modeling (PLS-SEM) to analyze four latent variables: librarian competence, interpersonal communication, student experience, and service quality. Data were collected through a five-point Likert-scale questionnaire administered to final-year students of Universitas Ciputra and analyzed using SmartPLS, with validity and reliability tests conducted to ensure the robustness of the measurement model. The results revealed that both librarian competence and interpersonal communication had significant direct effects on the quality of information literacy services, while the mediating role of student experience was not statistically supported, indicating that service quality is shaped more strongly by direct interactions than by mediated experiences. These findings underscore the importance of strengthening librarians’ professional competence and communication skills as key drivers of service quality, suggesting that higher education institutions should prioritize continuous training and professional development to optimize literacy services for final-year students. The following are appended: (1) Research instruments in the form of Likert-scale questionnaires; (2) Data processing procedures and SmartPLS outputs, including measurement and structural model testing; and (3) Additional statistical findings such as bootstrapping results and non-significant mediation analysis.